Je pense donc je fais: transcranial direct current stimulation modulates brain oscillations associated with motor imagery and movement observation - Lapenta, Olivia M.; Minati, Ludovico; Fregni, Felipe; Boggio, Paulo S. (Frontiers in Human Neuroscience, 2013)
Motor system neural networks are activated during movement imagery, observation and execution, with a neural signature characterized by suppression of the Mu rhythm. In order to investigate the origin of this neurophysiological marker, we tested whether transcranial direct current stimulation (tDCS) modifies Mu rhythm oscillations during tasks involving observation and imagery of biological and non-biological movements. We applied tDCS (anodal, cathodal and sham) in 21 male participants (mean age 23.8+3.06), over the left M1 with a current of 2mA for 20 minutes. Following this, we recorded the EEG at C3, C4 and Cz and surrounding C3 and C4 electrodes. Analyses of C3 and C4 showed significant effects for biological vs. non-biological movement (p=0.005), and differential hemisphere effects according to the type of stimulation (p=0.04) and type of movement (p=0.02). Analyses of surrounding electrodes revealed significant interaction effects considering type of stimulation and imagery or observation of biological or non-biological movement (p=0.03). The main findings of this study were (i) Mu desynchronization during biological movement of the hand region in the contralateral hemisphere after sham tDCS; (ii) polarity-dependent modulation effects of tDCS on the Mu rhythm, i.e. anodal tDCS led to Mu synchronization while cathodal tDCS led to Mu desynchronization during movement observation and imagery (iii) specific focal and opposite inter-hemispheric effects, i.e. contrary effects for the surrounding electrodes during imagery condition and also for inter-hemispheric electrodes (C3 vs. C4). These findings provide insights into the cortical oscillations during movement observation and imagery. Furthermore it shows that tDCS can be highly focal when guided by a behavioral task.